Programming Of Proforma Used in the Simulation of Solar Dryer - Isaac AJUNWA; Danjuma S. YAWAS; Dangana M. KULLA; Ibrahim U. IBRAHIM; Albright A. EDET; Inniyaka R. IRMIYA; Najib A. ISMAIL, (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
The need for simulation cannot be over-emphasized. Project feasibility births the need for simulation. The simulation, therefore, creates a research path to save cost, provide initial design data for a project, and ensuring the success of the project. One good tool for running a simulation with TRNSYS which is observed wanting in research works is developed proformas in FORTRAN/C++. This work, therefore, aims at creating or developing a programming proforma used in the simulation of the solar dryer with TRNSYS 16.1. This simulation tool was used to mimic real-time scenario of solar insolation on solar harvesters as well as other functions besides solar power drives was used to simulate the performance of a solar dryer with the proformas created with FORTRAN/C++ programming language. To achieve this, adopted and derived mathematical equations critical to the proformas functionality using the FORTRAN/C++ programming language were used. The system’s performance in terms of the moisture content, drying rate, collector efficiency, and drying efficiency modeled using FORTRAN and simulated in TRNYSIS 16.1 showed that 5.49%, 2.86×10-5 kg/s, 44.24%, and 29.38% were respectively obtained for the moisture content, drying rate, collector efficiency, and drying efficiency. When compared to the experimental values results shows there is a small difference between these performance parameters values and the Experimental values.